New Blasting Techniques to Eliminate Subgrade Drilling, Improve Fragmentation, Reduce Explosive Consumption and Lower Ground Vibrations - R. Frank Chiappetta (International Society of Explosives Engineers, 2004)
A new blasting technique has been developed by International Technologies, LLC. to eliminate subgrade drilling, lower ground vibrations, improve fragmentation and reduce explosive consumption. The new technique utilizes a uniquely designed borehole plug, with a bottom hole air deck and a predetermined stemming mass on top of the plug. This combination is referred to as the Power Deck?. Single holes and full scale tests were conducted by Blasting Analysis International, Inc. (BAI) to determine how the system works, the mechanisms behind its success and the best design parameters to use for the given rock conditions. Results have shown reduced or eliminated subgrade drilling, ground vibration reductions of up to 33%, reduced explosive consumption by 16 to 25%, and improved fragmentation by up to 25%. This paper summarizes the methodology, field test setups, analyzes procedures and results for one series of single hole and full-scale tests which were performed in a Pennsylvania, USA quarry.